ANALISIS USAHA PETERNAKAN BABI PADA PERUSAHAN â€œKASEWEANâ€ KAKASKASEN II KOTA TOMOHON - Warouw, Zadrak M; Panelewen, V V.J; Mirah, Arie D.P (Universitas Sam Ratulangi, 2014)
ABSTRACTPIG FARM ANALYSIS OF KASEWEAN COMPANY AT KAKASKASEN II OF TOMOHON MUNICIPALITY. The objective of this study were to find cost production, benefit and break even point of pig farming in Kasewean enterprise located in Tomohon city. The Results of the study showed that, Kasewean enterprise had breakeven Point on pig farming at 103 103 heads, and the income level was Rp. 178.509.314/period of production. Value of the breakeven point could be seen through the value Margin Of Safety (MOS) of 67.62%, meaning that if the rate of production decreased by 67.63%, the pig farm is still in state of breakeven point, then the MOS value can be explained by Return Of Invesment (ROI). ROI obtained a value of 1.51. This means that the use of capital (cost of production) on a pig farm â€œKasaweanâ€ in Tomohon already at efficient scale or provide the level of profit. Conclusions were (1) The average cost of production of pig farming in Kasewean company Tomohon was 1.136.863/head/production period consisted of a fixed cost of Rp. 278.093 of a fixed cost and Rp. 858.770/heads/production period of variable cost with the value of ROI was 1.51 which means the use of capital (cost of production) of pig farm on theâ€œKaseweanâ€ company in Tomohon already efficient, (2) Pig farm on the â€œkaseweanâ€ company obtained significant profit because the everage income was Rp. 580.932/head/production period and the average monthly profit was Rp. 15.539.943. and (3) Animal farm on â€œKaseweanâ€ company has reached the value above breakeven point of 103.92 on production volume of 103 units or heads with turnover level of Rp. 178.509.314/production periodKey Words : Pig farming, benefit, cost, breakeven point